2018
DOI: 10.4187/respcare.05953
|View full text |Cite
|
Sign up to set email alerts
|

Medication Regimens for Managing Acute Asthma

Abstract: Asthma exacerbation is defined as a progressive increase in symptoms of shortness of breath, cough, or wheezing sufficient to require a change in therapy. After ruling out diagnoses that mimic an asthma exacerbation, therapy should be initiated. Short-acting β agonists and short-acting muscarinic antagonists are effective as bronchodilators for asthma in the acute setting. Systemic corticosteroids to reduce airway inflammation continue to be the mainstay therapy for asthma exacerbations, and, unless there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…MgSO 4 is regularly used in clinical practice. The established indications of MgSO 4 include pre-eclampsia/eclampsia, arrhythmia, and asthma [12,13,14,15]. Although the present study and previous clinical and laboratory studies [21,22,23,24] have indicated that MgSO 4 may exert certain beneficial effects against pulmonary hypertension, evidence that conclusively supports the clinical use of MgSO 4 against pulmonary hypertension is not currently available [34].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…MgSO 4 is regularly used in clinical practice. The established indications of MgSO 4 include pre-eclampsia/eclampsia, arrhythmia, and asthma [12,13,14,15]. Although the present study and previous clinical and laboratory studies [21,22,23,24] have indicated that MgSO 4 may exert certain beneficial effects against pulmonary hypertension, evidence that conclusively supports the clinical use of MgSO 4 against pulmonary hypertension is not currently available [34].…”
Section: Discussionmentioning
confidence: 67%
“…Magnesium sulfate (MgSO 4 ) is a natural calcium antagonist [12]. MgSO 4 is used clinically for the treatment of pre-eclampsia/eclampsia, arrhythmia, and asthma [13,14,15,16]. Notably, MgSO 4 is a vasodilator [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the existing evidence does not provide support for the administration of helium-oxygen mixtures to all emergency department patients with asthma flare-up, with some evidence of certain beneficial effects in patients with more severe obstruction [114]. Very limited and sometimes anecdotic data are present for general anesthesia drugs, or propofol and ketamine [115]. Finally, the recent ERS document on NIV, given the uncertainty of evidence, was unable to offer a recommendation of the use of NIV for acute respiratory failure due to asthma [116].…”
Section: Acute Settingsmentioning
confidence: 99%
“…3 BA at remission (BA-R) is the absence of asthma symptoms for a period of time, 4 while BA at exacerbation (BA-E) is a progressive increase in asthma symptoms. 5 In recent years, the incidence and mortality rate of BA is on the rise due to the deterioration of environmental pollution, which adversely impacts the health condition and the quality of life of BA patients. 6,7 Therefore, seeking novel biomarkers for BA diagnosis and treatment is critical for BA patients.…”
Section: Introductionmentioning
confidence: 99%